2007
DOI: 10.3201/eid1304.061266
|View full text |Cite
|
Sign up to set email alerts
|

Influenza (H5N1) Viruses in Poultry, Russian Federation, 2005–2006

Abstract: Migrating waterfowl may be the primary source of influenza (H5N1) in western Siberia and the European part of the Russian Federation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…There is also little evidence of reassortment occurring in other regions affected by H5N1, with all genotypes detected beyond China having been previously detected there years in advance (de Benedictis et al, 2007; Bragstad et al, 2007; Li et al, 2004; Lipatov et al, 2007; Wang et al, 2008). It therefore appears that the ecology of poultry systems in southern China, which contain a diverse assemblage of aquatic and terrestrial birds that harbor co-circulating endemic populations of H9N2 and H6N1 viruses (Duan et al, 2008; Vijaykrishna et al, 2008), is unique in generating H5N1 reassortant viruses.…”
Section: Genomic Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also little evidence of reassortment occurring in other regions affected by H5N1, with all genotypes detected beyond China having been previously detected there years in advance (de Benedictis et al, 2007; Bragstad et al, 2007; Li et al, 2004; Lipatov et al, 2007; Wang et al, 2008). It therefore appears that the ecology of poultry systems in southern China, which contain a diverse assemblage of aquatic and terrestrial birds that harbor co-circulating endemic populations of H9N2 and H6N1 viruses (Duan et al, 2008; Vijaykrishna et al, 2008), is unique in generating H5N1 reassortant viruses.…”
Section: Genomic Diversificationmentioning
confidence: 99%
“…The H5N1 outbreak in geese and gulls at Qinghai Lake, China in 2005 was the first evidence of large-scale death from H5N1 virus in migratory birds (Chen et al, 2005). Closely related Clade 2.2 viruses were subsequently transmitted to Mongolia, Siberia, Central Asia, East and Western European countries, and Africa (de Benedictis et al, 2007; Bragstad et al, 2007; Chen et al, 2005; Coven, 2006; Gall-Recule et al, 2008; Lipatov et al, 2007; Onishchenko et al, 2006). Virological and serological studies have shown that migratory birds can be naturally infected by HPAI H5N1 viruses and that infected birds could survive and shed the virus during migration (Brown et al, 2006; Goletic et al, 2010; Keawcharoen et al, 2008; Marjuki et al, 2009; Saad et al, 2007).…”
Section: Virus Transmission and Outbreaksmentioning
confidence: 99%
“…This hypothesis was quickly adopted by various organizations such as the World Health Organization (2005). Some studies supported this hypothesis, declaring finding H5N1 virus in the excretion of sampled wild birds (Chen et al 2005(Chen et al , 2006aLiu et al 2005;Lipatov et al 2007). However, the methodology used in these studies has been questioned on several occasions (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Recent extensive surveillance studies suggested that wild migratory birds, showing ability to perpetuate LPAIVs in nature, are not competent as indefinite reservoirs of HPAIVs, carried by these infected hosts over small or moderate distances [17]. However, molecular evidences indicated that the HP H5N1 virus outbreaks occurred, in 2005 and 2006, in this Western Siberia area could have emerged from wild migratory birds [12]. In this context it is also notable that the HP H5N1 virus was isolated, in February 2012, from wild birds in India and Nepal [18], countries connected to the Novosibirsk Region by the Central Asian Flyway (Figure 1) [7].…”
Section: Introductionmentioning
confidence: 94%